Influence of Age on Warfarin Dose, Anticoagulation Control, and Risk of Hemorrhage. Issue 6 (27th February 2018) - Shendre, Aditi; Parmar, Gaurav M.; Dillon, Chrisly; Beasley, Timothy Mark; Limdi, Nita A.
Abstract : Objective: We assessed the influence of age on warfarin dose, percentage time in target range (PTTR), and risk of major hemorrhage. Design: Warfarin users recruited into a large prospective inception cohort study were categorized into three age groups: young (younger than 50 yrs), middle aged (50–70 yrs), and elderly (older than 70 yrs). The influence of age on warfarin dose and PTTR was assessed using regression analysis; risk of major hemorrhage was assessed using proportional hazards analysis. Models were adjusted for demographic, clinical, and genetic factors. Setting: Two outpatient anticoagulation clinics. Participants: A total of 1498 anticoagulated patients. Outcomes: Warfarin dose (mg/day), PTTR, major hemorrhage. Results: Of the 1498 patients, 22.8% were young, 44.1% were middle aged, and 33.1% were elderly. After accounting for clinical and genetic factors, compared with young warfarin users, warfarin dose requirements were 10.6% lower among the middle aged and an additional 10.6% lower for the elderly. Compared with young patients, middle‐aged and elderly patients spent more time in target international normalized ratio (INR) range (p<0.0001), despite having fewer INR assessments (p<0.0001). Compared with young warfarin users, absolute risk of hemorrhage was marginally higher among the middle aged (p=0.08) and significantly higher among the elderly (p=0.016). Compared with young warfarin users, after adjustment, the relative risk of hemorrhage increased by 31% for each age category (p=0.026). Conclusions: In a real‐world setting, despite achieving better anticoagulation control, elderly patients had a higher risk of major hemorrhagic events. As the population ages and the candidacy for oral anticoagulation increases, strategies that mitigate the elevated risk of hemorrhage need to be identified.